Involvement of CD14 and Toll-Like Receptors in Activation of Human Monocytes by Aspergillus fumigatus Hyphae - Wang, J. E. (American Society for Microbiology, 2001)
Invasive fungal infections represent an increasing problem associated with high mortality. The present study was undertaken to identify leukocyte subsets that are activated by hyphal fragments in a whole-human-blood model, as well as to examine the involvement of CD14 and Toll-like receptors (TLRs) in activation of monocytes by hyphae. Incubation of whole human blood with hyphal fragments from Aspergillus fumigatus and Scedosporium prolificans for 6 h caused induction of mRNAs for tumor necrosis factor alpha (TNF-α), interleukin-1β (IL-1β), and IL-6 in T cells, B cells, and monocytes, but not in granulocytes, as analyzed by reverse transcription-PCR with mRNA isolated from very pure populations of these leukocyte subsets. In primary adherent human monocytes, induction of TNF-α by hyphal fragments was dependent on plasma. Heat treatment of plasma at 56°C for 30 min strongly reduced the ability of plasma to prime for activation. Pretreatment of human monocytes with different concentrations (1, 3, and 10 μg/ml) of monoclonal antibody (MAb) HTA125 (anti-TLR4) or MAb 18D11 (anti-CD14) for 30 min inhibited the release of TNF-α induced by hyphal fragments in a dose-dependent manner. Maximal inhibitions of 35 and 70% were obtained with 10 μg of HTA125 and 18D11 per ml, respectively. In contrast, pretreatment with MAb TL2.1 (anti-TLR2) did not affect signaling induced by hyphae. Pretreatment with the lipid A antagonist B975 blocked lipopolysaccharide signaling but did not inhibit TNF-α production induced by hyphal fragments. Our results suggest that T cells, B cells, and monocytes are involved in the innate immune response to invasive fungal pathogens and that serum components are relevant for activation of monocytes by hyphae. CD14 and TLR4 may be involved in signaling of Aspergillus hyphae in monocytes, but further studies to elucidate this issue are warranted.